Life in Morocco and glimpses beyond - Meakin, Budgett (Chatto & Windus, 1905)
"The present volume gathers together from many quarters sketches drawn under those circumstances, supplemented by a résumé of recent events and the political outlook, together with three chapters viii., xi., and xiv. contributed by his wife, whose assistance throughout its preparation he has once more to acknowledge with pleasure. To many correspondents in Morocco he is also indebted for much valuable up-to-date information on current affairs, but as most for various reasons prefer to remain unmentioned, it would be invidious to name any. For most of the illustrations, too, he desires to express his hearty thanks to the gentlemen who have permitted him to reproduce their photographs."--Foreword (p. vii)